Analisis Triple Helix Peran Stakeholder Dalam Meningkatkan Penggunaan Motor Listrik Di Indonesia - Chadziqatun Najilatil Mazda; Dwi Agustina Kurniawati; Ira Setyaningsih (Jurnal Teknologi, Fakultas Teknologi Industri, Institut Sains & Teknologi AKPRIND Yogyakarta, 2022)
In this modern era, the use of electric vehicles is not a new thing. The grand strategy of energy national (GSEN) has fourteen strategic programs to be implemented, one of them is increasing the use of battery- electric vehicles motorized, in order to reduce the imports of fuel oil (BBM) and LPG as well as equitable electrification in Indonesia. This program needs to support by cooperation and role contribution from participants (stakeholders). This study was conducted to determine the role of stakeholders to increasing the use of electric motors in Indonesia using a triple helix methode. The data collection was carried out through interviews and documentation studies. The analyze data was use miles and hubberman. The results showed that based on the triple helix analysis, there were 3 stakeholders involved to increasing the use of electric motors in Indonesia. There were universities, industry and government. The universities have a role in conducting research and development for electric motor products, this can be done through final project research or providing research grants the development electric motors topic. The industry has a role in producing electric motors, for example Gesit Companies which produces electric motors, and also raw materials industry and spare part industry as well as component of electric motors. The government has a role in regulations through policies of equitable electrification motor vehicles in Indonesia. One of them is from the Minister of Transportation Regulation (Permenhub) Number 65 of 2020 concerning the conversion of fuel motorcycles into battery-electric motorcycles.